PENGAPLIKASIAN KARAKTER NABI IBRAHIM AS PADA ASPEK PERKEMBANGAN PENDIDIKAN USIA DINI : (Implementasi Tiga Karakter; Shiddiq, Rasional, dan Pemberani) - Surasman, Otong (Ta'dibiya, 2024)
This research will examine the three characters of Prophet Ibrahim AS in the holy book Al-Qur'an (siddiq, rational, and brave), as the basis for educational values ​​at an early age, with the hope that in the future a generation will be created with honest characters. in all things, think positively and act positively, and are also able to convey truthful values ​​in order to improve the nation's character. This research uses a qualitative approach by conducting an in-depth study of the text of the holy book Al-Qur'an as the main source, which is closely related to the three characters of Prophet Ibrahim AS, shidiq, rational and brave in life. Apart from the holy book Al-Qur'an as the main reference, we also use the literature of tafsir books to make it easier to understand the character of Prophet Ibrahim AS contained in the holy book Al-Qur'an. The main aim of this research is to obtain actual and factual information about the three characters of Prophet Ibrahim AS, Shidiq, rational and brave, then use it as a reference as the main principle in developing educational values ​​at an early age. The temporary conclusion is that by applying the three characters of Prophet Ibrahim AS (Siddiq, Rational and Courageous), to the values ​​of early childhood education, generations will emerge who can understand the direction of life, who are able to take responsibility for every step of their life, by thinking long and being able to uphold truth and justice.